2015
DOI: 10.1002/anie.201508651
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Fishing for Calixarene Partners by a Chemoproteomic Approach

Abstract: MS-based chemical-proteomics technology is introduced herein as a third general strategy to study the biomolecular recognition properties of given calixarene derivatives. In particular, we demonstrate that a simply designed calix[4]arene derivative 1 a bearing acetamido groups at the exo rim (pAC), when linked to a solid support, is able to fish out a specific protein (PDI protein) from a crude extract of HeLa cells. Western blot and surface plasmon resonance studies confirmed the direct interaction between PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Following this approach, Hamilton and co-workers introduced at the upper rim of a conformationally-blocked, cone-shaped calix [4]arene scaffold four peptide functions which were able to establish multiple interactions with a PDGF growth factor, thus giving rise to antiangiogenic activity in vivo [11][12][13]. In another work, docking studies suggested that multiple H-bond and hydrophobic interactions play a crucial role in the interaction between a p-acetamidocalix [4]arene derivative and the protein disulfide isomerase (PDI), which is highly expressed in cancer cell types, including lung, brain, ovarian, melanoma, and prostate [14]. In a further work, in vitro studies [15] showed that conformationally-blocked calix [4]arene derivatives bearing aromatic naphthyl, pyrenyl, and aryl groups at the upper rim were able to inhibit HDAC enzymes, while docking calculations suggested that multiple hydrophobic interactions between the aromatic arms and the hydrophobic pockets close to the active site of the enzymes were essential for the stabilization of the HDAC-calixarene complex.…”
Section: Introductionmentioning
confidence: 99%
“…Following this approach, Hamilton and co-workers introduced at the upper rim of a conformationally-blocked, cone-shaped calix [4]arene scaffold four peptide functions which were able to establish multiple interactions with a PDGF growth factor, thus giving rise to antiangiogenic activity in vivo [11][12][13]. In another work, docking studies suggested that multiple H-bond and hydrophobic interactions play a crucial role in the interaction between a p-acetamidocalix [4]arene derivative and the protein disulfide isomerase (PDI), which is highly expressed in cancer cell types, including lung, brain, ovarian, melanoma, and prostate [14]. In a further work, in vitro studies [15] showed that conformationally-blocked calix [4]arene derivatives bearing aromatic naphthyl, pyrenyl, and aryl groups at the upper rim were able to inhibit HDAC enzymes, while docking calculations suggested that multiple hydrophobic interactions between the aromatic arms and the hydrophobic pockets close to the active site of the enzymes were essential for the stabilization of the HDAC-calixarene complex.…”
Section: Introductionmentioning
confidence: 99%
“…Calixarene macrocycles [ 22 ] have found numerous applications in several areas of supramolecular chemistry, such as (bio)molecular recognition [ 23 ] and catalysis [ 24 ]. The widespread use of the calixarene derivatives is due to their convenient synthesis and to their chemical and conformational versatility [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The topic is particularly attractive in view of 1) the wide variety of ligands provided by supramolecular chemistry,a nd 2) the continuing challengeo ftargeting protein surfaces, with their unique patchworks of hydrophobic, polar and charged regions. Efforts to approximate protein surfaces with supramolecular ligands have involved calixarenes, [1,[5][6][7][8][9][10][11][12] crown ethers, [13][14][15] curcurbiturils, [16][17][18][19] foldamers, [20][21][22][23] porphyrins [24][25][26][27][28][29][30][31] andt weezers. [2,[31][32][33] Recent attention has focusedo n the cationic side chains of lysine and arginine as potentialt argets that protrudei nvitinglyf rom the protein surface.…”
Section: Introductionmentioning
confidence: 99%